Counteracting Protein Kinase Activity in the Heart: The Multiple Roles of Protein Phosphatases - Weber, Silvio; Meyer-Roxlau, Stefanie; Wagner, Michael; Dobrev, Dobromir; El-Armouche, Ali (Frontiers in Pharmacology, 2015)
Decades of cardiovascular research have shown that variable and flexible levels of protein phosphorylation are necessary to maintain cardiac function. A delicate balance between phosphorylated and dephosphorylated states of proteins is guaranteed by a complex interplay of protein kinases (PK) and phosphatases. Serine/threonine phosphatases, in particular members of the protein phosphatase (PP) family govern dephosphorylation of the majority of these cardiac proteins. Recent findings have however shown that PPs do not only dephosphorylate previously phosphorylated proteins as a passive control mechanism but are capable to actively control PK activity via different direct and indirect signaling pathways. These control mechanisms can take place on (epi-)genetic, (post-)transcriptional and (post-)translational levels. In addition PPs themselves are targets of a plethora of proteinaceous interaction partner regulating their endogenous activity, thus adding another level of complexity and feedback control towards this system. Finally, novel approaches are underway to achieve spatiotemporal pharmacologic control of protein phosphatases which in turn can be used to fine-tune misleaded protein kinase activity in heart disease. Taken together, this review comprehensively summarizes the major aspects of PP-mediated PK regulation and discusses the subsequent consequences of deregulated PP activity for cardiovascular diseases in depth.